Evaluation of basal heave factor of safety for excavation in clays - Lim, Wei Ting. (2012)
For braced excavation in clays, one major design consideration is the determination of basal heave Factor of Safety. There are many conventional formulas that have been proposed to evaluate the Factor of Safety against basal heave failure. The methods proposed by Terzaghi, and Bjerrum & Eide remain the two most common methods to evaluate the Factor of Safety (FS) for wide and narrow excavations respectively. However, such conventional methods do not consider factors such as depth of embedment (D) and wall stiffness (EI). In fact, these formulas were developed before the introduction of stiffer walls.